2020
DOI: 10.5093/pi2020a11
|View full text |Cite
|
Sign up to set email alerts
|

Are Interventions with Batterers Effective? A Meta-analytical Review

Abstract: Intervention programs for batterers have been the subject of controversy ever since their conception. These interventions have been open to criticism from both a restorative perspective and a feminist perspective demanding resources should be allocated to victims, not to batterers. Such criticism, however, comes into direct conflict with the legal and judicial mandate of prison institutions that are obliged

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 48 publications
1
63
0
7
Order By: Relevance
“…Both sources of bias pollute the results in the proximal outcomes to some extent. Finally, the effect size in most analyses ranged from low to moderate, which is consistent with systematic reviews and meta-analyses in this field, where the effectiveness of intervention programmes has been assessed (Arce et al, 2020;Babcock et al, 2004;Feder & Wilson, 2005;Santirso, Gilchrist, Lila, & Gracia, 2020).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Both sources of bias pollute the results in the proximal outcomes to some extent. Finally, the effect size in most analyses ranged from low to moderate, which is consistent with systematic reviews and meta-analyses in this field, where the effectiveness of intervention programmes has been assessed (Arce et al, 2020;Babcock et al, 2004;Feder & Wilson, 2005;Santirso, Gilchrist, Lila, & Gracia, 2020).…”
Section: Discussionsupporting
confidence: 74%
“…Ever since these programmes were set up, several studies have been conducted to evaluate their effectiveness, but no consensus has been reached about the intervention effect on changing batterers' behaviour (Bowen, 2011;Gondolf, 2012). Several meta-analysis and systematic reviews have attempted to solve this problem by compiling the results of available research in this field (e.g., Arango et al, 2014;Arce, Arias, Novo & Fariña, 2020;Babcock, Green, & Robie, 2004;Eckhardt et al, 2013;Feder & Wilson, 2005). The main findings show small and/or moderate size effects, and problems hindering their effectiveness, such as the high dropout rates and lack of adherence to treatment (Arango et al, 2014;Eckhardt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1974 doctrine heralding Nothing works in the rehabilitation of criminal offenders in Martinson's meta-analytical review that found no positive intervention effects, substantial progress has been made in the treatment of criminal offenders. These have been underpinned by models of additive and accumulative deficits, needs or weakness aimed at identifying specific deficiencies of each delinquent to design a bespoke treatment program targeting the rehabilitation of the criminal offender's deficits, needs or weaknesses (Arce, Arias, Novo, & Fariña, 2020;Carbajosa, Catalá-Miñaña, Lila, & Gracia, 2017;Gannon, Olver, Mallion, & James, 2019;Redondo, Sánchez-Meca, & Garrido, 2002). Psychosocial treatment has been the primary intervention type, particularly cognitive-behavioural treatment programs, which has proven to be the most effective intervention program for general delinquency (Gannon et al, 2019;Redondo et al, 2002), and for specific crime typologies such as sexual (Schmucker & Lösel, 2015), and IPV offenders (Arce et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These offenders are driven by internal, stable, and global cognitions, known as toxic cognitions that are highly refractory to intervention (Maruna, 2004). Thus, in terms of recidivism, treatment of batterers is among the least efficacy (Arce et al, 2020;Arias, Arce, & Vilariño, 2013;Babcock, Green, & Robie, 2004) as IPV offenders are not susceptible to spontaneous retraction (Martín, Padrón, & Redondo, 2019). Moreover, the efficacy of interventions according to Official Records (ORs) ranged from 5% (Babcock et al, 2004) to 20% (Arias et al, 2013), whereas as in Couple Reports (CRs) it was null (Arce et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recidivism in delinquency is related to deficits in non-criminogenic needs such as psychological adjustment that explained 19.5% of the risk of recidivism in delinquency (Basanta et al, 2018), with externalizing disorders (d = 0.415, explaining 4.1% of recidivism), comorbid -internalizing and externalizing-( d = 0.366, explaining 3.2% of recidivism) (Wibbelink et al, 2017), and social skills (e.g., consideration for others; selfcontrol in social relations) explaining 21.6% of the risk of recidivism in delinquency (Basanta et al, 2018); thus, these factors were not the root cause of delinquency, but facilitated recidivism. Moreover, these estimates explaining recidivism were underestimated given that the measures of recidivism in Official Records fail to identify most real recidivism (Arce, Arias, Novo, & Fariña, 2020). Hence, interventions must also target these needs.…”
Section: Introductionmentioning
confidence: 99%